VALIDITY OF TRANSABDOMINAL ULTRASOUND SCAN IN THE PREDICTION OF UTERINE SCAR THICKNESS - Sarwar, Iram; Akram, Faiza; Khan, Attiya; Malik, Saqib; Islam, Ansa; Khan, Kinza (Journal of Ayub Medical College Abbottabad, 2020)
Background: Caesarean section rate is increasing throughout the world, which increases the risk of complications in subsequent pregnancy with increased maternal and foetal morbidity and mortality. There is risk of uterine rupture in subsequent pregnancy with trial of labour after caesarean section (TOLAC). Therefore, accurate prediction of uterine rupture can be of significant value during the management of subsequent pregnancies after previous caesarean delivery. The aim of this study was to evaluate the accuracy of prenatal transabdominal sonography in determining the lower uterine segment thickness in women with previous caesarean section, to document relevant risk factors in the obstetric history of subjects predisposing to uterine scar rupture and to define a cut-off value of uterine thickness for prediction of uterine rupture. Methods: This cross-sectional validation study was conducted in the Department of Obstetrics and Gynaecology, Ayub Teaching Hospital, Abbottabad from May to October 2017.Transabdominal ultrasound was carried out in all patients before labour for the measurement of uterine scar thickness. Patients were followed till caesarean section and intraoperative findings were recorded. Results: A total of 117 patients were enrolled. Out of these 33% had thin or dehiscence/rupture scar. At the cut-off value of ‰¤5 mm the sensitivity was 76.9%, specificity 48.7% and accuracy was 58.12%. No significant association was found between clinical features and scar dehiscence/rupture. Conclusion: No definite USG cut-off limit could be established to provide guidance regarding the clinical decision of opting for VBAC or repeat caesarean/section; scar thicknesses ‰¤5.0 mm should be judged cautiously. Keywords: Caesarean section; ultrasonography; uterine scar thickness; VBAC; TOLAC